Unlocking sustainable success: the transformative impact of CSR on hotel performance - Pham T.H Dung; Hien Thanh Hoang; Nguyen Phi Son (Cogent Social Sciences, 2024)
This study explores the impact of Corporate Social Responsibility (CSR) on hotel performance in Vietnam’s South-Central Coast, highlighting the role of employee engagement, corporate reputation, and pro-environmental behavior. Analyzing data from 646 hotel managers through structural equation modeling, it finds that CSR not only directly improves performance but is also further enhanced by employee engagement and reputation, with pro-environmental behavior serving as a key moderating factor. These insights offer valuable strategies for leveraging CSR towards sustainable development and efficiency in the hospitality sector.